1993
DOI: 10.1002/ijc.2910550423
|View full text |Cite
|
Sign up to set email alerts
|

Production of monoclonal antibodies to human estrogen‐receptor protein (ER) using recombinant ER (RER)

Abstract: Two monoclonal antibodies (MAbs), IC5 and ID5, were produced using spleen cells from BALB/c mice immunized with recombinant estrogen-receptor protein (RER). On immunoblotting, both MAbs reacted with the 67-kDa polypeptide chain obtained by transformation of E. coli and transfection of COS cells with plasmid vectors expressing ER. The epitopes of both MAbs were in the N-terminal domain (A/B region) of the receptor. In normal human tissues, IC5 and ID5 reacted with cells known to contain large amount of ER, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 15 publications
(20 reference statements)
1
68
1
Order By: Relevance
“…Second, the interpretation of the staining at the cellular level is easier in paraffin wax sections compared with autoradiograms and immunohistochemically stained frozen sections. Finally, the commercially available ER-antibody used, which has been documented as ER-α-specific by Saati et al (1993) and Pettersson et al (1997) has made it possible to immunodetect ER-α specifically. The quality of the immunohistochemical method used in the present study is believed to be sufficient for evaluating the distribution of ER-α, since the immunostaining is exclusively nuclear and, in both kinds of negative control sections, immunoreaction is absent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the interpretation of the staining at the cellular level is easier in paraffin wax sections compared with autoradiograms and immunohistochemically stained frozen sections. Finally, the commercially available ER-antibody used, which has been documented as ER-α-specific by Saati et al (1993) and Pettersson et al (1997) has made it possible to immunodetect ER-α specifically. The quality of the immunohistochemical method used in the present study is believed to be sufficient for evaluating the distribution of ER-α, since the immunostaining is exclusively nuclear and, in both kinds of negative control sections, immunoreaction is absent.…”
Section: Discussionmentioning
confidence: 99%
“…The ER-antibody was monoclonal and raised to the N-terminal (A/B) region of the human ER-α receptor (DAKO A/S, Glostrup, Denmark). Western blot analysis of proteins extracted from human endometrium showed that the antibody reacts with a single band of 67 kDa representing ER-α (Saati et al, 1993). Furthermore, the ER-antibody does not crossreact with ER-β (Pettersson et al, 1997).…”
Section: Immunohistochemistrymentioning
confidence: 97%
“…The non-immunoglobulinproducing myeloma cell line P3 ϫ 63 Ag8-653 was used as a fusion partner. Fusions were performed using standard techniques (33,34). Supernatants were tested for antibody-binding activity by ELISA and by indirect immunoperoxidase method on frozen sections of human pancreas and tonsil.…”
Section: Production Of Pnl2 Mabmentioning
confidence: 99%
“…Our aim was to investigate these correlations using a newly developed monoclonal antibody against ER, ER-ID5 (13,14), in a breast cancer series, where all patients had been treated with adjuvant tamoxifen. The findings were also related to other prognostic factors, particularly to the histopathological pattern.…”
mentioning
confidence: 99%